Goji berries superfood – contributions for the characterisation of proteome and IgE-binding proteins - Teixeira, Sandrina (2020)
Goji berries’ bioactive compounds, which allowed classifying them as superfruits, led to an enormous increase of its consumption in western countries. However, the potential risk of allergy is a concern. In this study, we aimed to characterise the proteome of goji berries (Lycium barbarum) and identify proteins with putative role in the allergic reaction (IgE-binding proteins). We firstly used twodimensional (2D) gel electrophoresis followed by mass spectrometry (MS) to characterise goji berries’ proteome, and then Immunoblot reactivity with plasma from tomato and potato (same botanical family, Solanaceae) allergic individuals was assessed to characterise goji berries IgE-binding proteins. An inhibition assay was further performed to evaluate cross-reactivity among potato, tomato and goji berries. We significantly identified 93 out of the 180 MS analysed spots, corresponding to 29 protein functions. From these, 11 could be identified as goji berries IgE-binding proteins. We further demonstratedcross-reactivity between goji berries, tomato and potato.